RETRACTED: Pengaruh Metode Gerak dan Lagu Terhadap Perkembangan Sosial dan Emosional Anak di TK Kota Padang - Yolanda Mustika Fitri; Nurhafizah Nurhafizah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
RETRACTION TO: Fitri, Y.M., Nurhafizah, N (2022). Pengaruh Metode Gerak dan Lagu Terhadap Perkembangan Sosial dan Emosional Anak di TK Kota Padang. Jurnal Obsesi: Jurnal Pendidikan Anak Uisia Dini, 6 (5), 4831-4838.This article has been retracted by Publisher based on the following reason:The Editor of Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini found the double publication in the article publishing due to article's content similarity published in https://jbasic.org/index.php/basicedu/article/view/779Fitri, Y., Nurhafizah, N. (2021). Pengaruh Metode Gerak dan Lagu Terhadap Perkembangan Sosial dan Emosional Anak di Kota Padang. Jurnal Basicedu, 5(2), 636-642. https://doi.org/10.31004/basicedu.v5i2.779One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process